Delayed Rebound of Glycemia During Recovery Following Short-Duration High-Intensity Exercise: Are There Lactate and Glucose Metabolism Interactions? - Messonnier, Laurent A.; Chatel, Benjamin; Emhoff, Chi-An W.; Blervaque, Léo; Oyono-Enguéllé, Samuel (Frontiers in Nutrition, 2021)
Lactate constitutes the primary gluconeogenic precursor, accounting for 60-80% of the total gluconeogenic flux in healthy humans at rest and during exercise. Data on the interactions between lactate and glucose metabolisms during recovery are on the contrary relatively sparse. The aim of the present study was to describe blood glucose and lactate concentration curves during recovery following high-intensity exercises. Fifteen healthy Cameroonian subjects took part in the study and performed successively i) an incremental exercise up to exhaustion to determine maximal work rate (Pmax) and ii) a 2-min 110% Pmax exercise after which blood lactate and glucose concentrations were measured during the 80-min passive recovery. Blood lactate concentrations displayed the classical biphasic curve while blood glucose concentrations displayed a singular shape. After an initial and transitory burst followed by a return to normal and resting blood glucose concentration, a delayed rebound of glycaemia was observed. This rebound occurred 20 to 45 min into recovery and peaked 40 to 70 min into recovery at 6 to 7.5 mmol.L-1. Interestingly, the earlier the lactate decay, the earlier the rebound of glycaemia. In conclusion, although it has yet to be confirmed by mechanistic studies, the most likely explanation for the glucose kinetics observed in the present study is an activation of gluconeogenesis, stimulated by the abundance of substrate (lactate) and catecholamines following this type of short high-intensity exercises. Further studies are warranted.